The influence of self-efficacy, field work practice and family socio-economic status on the work readiness - Trissa Oktalina Cahyani; Candra Vionela Merdiana; Sukardi (www.amertainstitute.com, 2024)
This study aims to examine the effect of self-efficacy, field work practices, and family socioeconomic status on job readiness. The research was conducted at Ahmad Dahlan University, Yogyakarta, with the population consisting of all 2019 Management Study Program students, totaling 313 individuals. The sample size was 196 students, selected using a non-probability sampling method with a purposive sampling technique. Data for this research were analyzed using SPSS version 25. The results indicate that self-efficacy has a positive and significant effect on job readiness, and field work practices also have a significant positive impact on job readiness. However, family socioeconomic status shows a negative but significant influence on job readiness. Furthermore, a simultaneous test reveals that the combined variables of self-efficacy, field work practices, and family socioeconomic status collectively influence job readiness. These findings suggest that fostering students' self-efficacy and enhancing field work practice programs can improve their job readiness. Meanwhile, the impact of family socioeconomic status highlights the importance of providing additional support to students from lower socioeconomic backgrounds to ensure equitable preparation for the workforce.